Epoxy resin composite material with inorganic material and preparation method thereof
By using montmorillonite to prepare the putaway inorganic material and mix it with epoxy resin, the problems of insufficient toughness and poor aging resistance of the epoxy resin cured substances are solved, and the effect of improving the toughness and aging resistance of the material is achieved.
Patent Information
- Application Number
- CN202411699390.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-05-13
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The lack of toughness and poor aging resistance of epoxy resin cured substances lead to certain defects in practical applications.
Montmorillonite is used as an inorganic material, and by reacting with acid chloride compounds, diallyl isocyanurate and hindered phenol antioxidants, the core inorganic material is prepared, and mixed with epoxy resin, curing agent and curing accelerator to form a composite material.
By forming a hydrogen bonding network and a physical crosslinking core, the toughness and mechanical properties of the epoxy resin composite are improved, while improving its aging resistance to yellowing and extending the service life of the material.
Smart Images

Figure BDA0005152876940000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to an epoxy resin composite material with inorganic materials and a preparation method thereof. Background Art
[0002] Epoxy resin has excellent chemical resistance, physical and mechanical properties, electrical insulation and processing properties, and can form a strong connection with various materials. Therefore, it is widely used in coatings, adhesives, injection molding materials and other fields, and occupies an important position in various fields of the national economy. However, the cured product formed after epoxy resin is cured is relatively brittle, has poor toughness, and has poor aging resistance. It is easy to produce aging and yellowing, which in turn affects the appearance of the cured product. Therefore, its application in the fields of building exterior wall coatings has gradually been greatly restricted. Therefore, in practical applications, it is often necessary to optimize the formula and use various additives to compound with epoxy resin to form epoxy resin composite materials, and use the various reinforcing effects of additives to improve the comprehensive properties of epoxy resin such as toughness and aging resistance.
[0003] The invention patent with application number CN202210586729.6 discloses an epoxy resin for closed combination electrical appliances and a preparation method thereof. By using antioxidant 703 as an additive and mixing it with epoxy resin, the mechanical strength of the product can be less affected while achieving the effect of anti-aging and yellowing. However, the patent does not focus on solving the problem of insufficient toughness of epoxy resin cured products, and its products still have certain defects in practical applications.
[0004] Introducing inorganic nanomaterials into epoxy resin is an effective modification method, because the high activity, large specific surface area and strong interface effect of nanomaterials improve the comprehensive performance of epoxy resin; the nanomaterials currently used are mostly nanopowders, such as nano silicon dioxide, nano titanium dioxide, etc., but since these commercial materials with nanometer particle sizes are easy to agglomerate, it is quite difficult to achieve true nano dispersion in epoxy resin. Montmorillonite, known as a natural nanomaterial, is a silicate with a layered structure. Its structural lamellae are all nanometer-sized, and there are exchangeable cations between the lamellae. Through ion exchange reaction, that is, organic treatment, organic ions with larger volume than the above ions can be introduced, which can increase the interlayer spacing of montmorillonite lamellae; the present invention provides an epoxy resin composite material with inorganic materials, which can utilize the excellent comprehensive performance of montmorillonite materials to improve the problems of insufficient toughness and poor aging resistance of epoxy resin, and promote the further application and development of epoxy resin. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] In view of the deficiencies in the prior art, the present invention provides an epoxy resin composite material with inorganic materials and a preparation method thereof, which solves the problems of insufficient toughness and poor aging and yellowing resistance of epoxy resin cured products.
[0007] (II) Technical solution
[0008] An epoxy resin composite material with inorganic materials comprises the following raw materials in parts by weight: 85-95 parts of epoxy resin, 5-10 parts of shell-core inorganic materials, 12-20 parts of curing agents, and 5-10 parts of curing accelerators.
[0009] The core-shell inorganic material is prepared by the following method:
[0010] Step 1: Mix montmorillonite and tetrahydrofuran, stir to form a uniform dispersion, add acyl chloride compounds to the dispersion, pass nitrogen protection, start stirring, stir at room temperature for 4-8 hours, centrifuge to obtain a solid product, wash and dry to obtain intermediate material ①.
[0011] Step 2: Disperse the montmorillonite intermediate material ① in 1,4-dioxane, add diallyl isocyanurate and the catalyst and stir evenly, under nitrogen protection, at a reaction temperature of 60-70°C, stir and react for 4-6 hours, then cool and discharge the material to obtain the intermediate material ②.
[0012] Step 3: Mix the intermediate material ② with ethanol, stir until evenly distributed, then add 2-(2-hydroxy-3-tert-butyl-5-methylbenzyl)-4-methyl-6-tert-butyl acrylate and stir evenly, raise the system temperature to 70-75°C, pass nitrogen to deoxygenate, then add the initiator, react at a constant temperature for 2-6 hours, separate the material, and obtain the core-shell inorganic material through washing and drying processes.
[0013] Preferably, the epoxy resin is any one of E51 epoxy resin or E44 epoxy resin.
[0014] Preferably, the curing agent is any one of polyamide or polyetheramine D400.
[0015] Preferably, the curing accelerator is any one of imidazole or tertiary amine
[0016] Preferably, in the first step, the average particle size of the montmorillonite is 5 um.
[0017] Preferably, in the first step, the acyl chloride compound is any one of bromoacetyl chloride, 3-bromopropionyl chloride or 4-bromobutyryl chloride.
[0018] Preferably, in the second step, the catalyst is any one of triethylamine or pyridine.
[0019] Preferably, in the third step, the initiator is any one of azobisisobutyronitrile, azobisisovaleronitrile or azobisisoheptanenitrile.
[0020] In the above scheme, the surface of montmorillonite contains Si-OH, which can undergo a condensation reaction with the acyl chloride group in the structure of acyl chloride compounds such as bromoacetyl chloride, thereby modifying the halogen group on the surface of montmorillonite to obtain an intermediate material ①. Under the action of a catalyst, the halogen group can undergo a nucleophilic substitution reaction with the secondary amine in the structure of diallyl isocyanurate, thereby modifying a large number of unsaturated alkenyl functional groups on the surface of montmorillonite to obtain an intermediate material ②. With these unsaturated alkenyl functional groups as initiation sites, under the initiation action of an initiator, 2-(2-hydroxy-3-tert-butyl-5-methylbenzyl)-4-methyl-6-tert-butyl phenyl acrylate can be in-situ polymerized on the surface of montmorillonite to form a core-shell montmorillonite with a polymer hindered phenol antioxidant layer on the surface, i.e., a core-shell inorganic material.
[0021] A method for preparing an epoxy resin composite material with an inorganic material comprises the following steps:
[0022] Step 1: Take 10 parts by weight of epoxy resin and curing agent, place them in a stirring kettle, stir them at a temperature of 60-70°C for 1-2 hours, add 10 parts by weight of shell-core inorganic material, continue stirring for 1-2 hours, then add 10 parts by weight of curing accelerator, stir and mix for 0.5-1 hour, and then stand to degas to form a premixed material;
[0023] Step 2: Pour the premixed material into the mold, raise the temperature to 90-100°C, maintain it for 2-3 hours, then raise the temperature to 140-150°C, maintain it for 2-3 hours, and wait for the material to cool naturally to obtain the epoxy resin composite material.
[0024] (III) Beneficial technical effects
[0025] The present invention prepares a core-shell inorganic material with montmorillonite as the core and a polymer hindered phenol antioxidant layer as the shell. Since the core layer structure contains abundant lipid bonds, hydrogen bonds can be generated with hydroxyl groups in the epoxy resin structure, so in the curing process of the epoxy resin, a hydrogen bond association network can be formed with the epoxy resin, effectively improving the interface performance of the inorganic material and the epoxy resin, so that it can be evenly distributed in the epoxy resin network structure in the form of a physical cross-linking core. Therefore, when the epoxy resin composite material is subjected to external forces, the generated stress can be distributed to the polymer network through the physical cross-linking core, forming the effect of stress transfer and dispersion, thereby avoiding the phenomenon of material damage caused by stress concentration, and is conducive to improving the toughness and mechanical properties of the epoxy resin composite material. At the same time, the core layer structure in the core-shell inorganic material contains a hindered phenol antioxidant, which can effectively improve the anti-aging yellowing performance of the epoxy resin composite material, and due to the confining effect of the hydrogen bond association network on the core-shell inorganic material, the antioxidant cannot migrate and precipitate, which can ensure that the epoxy resin composite material has a long-term anti-aging yellowing effect. DETAILED DESCRIPTION
[0026] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. Preferred embodiments of the present invention are given below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0027] Example 1
[0028] An epoxy resin composite material with inorganic materials comprises the following raw materials in parts by weight: 85 parts of E51 epoxy resin, 5 parts of shell-core inorganic material, 12 parts of curing agent polyamide, and 5 parts of curing accelerator imidazole;
[0029] The epoxy resin composite material is prepared by the following method:
[0030] Step 1: Take parts by weight of E51 epoxy resin and curing agent polyamide, place them in a stirring kettle, stir them at a temperature of 60° C. for 1 hour, add parts by weight of shell-core inorganic material, continue stirring for 1 hour, then add parts by weight of curing accelerator imidazole, stir and mix for 0.5 hours, and then stand to degas to form a premixed material;
[0031] Step 2: Pour the premixed material into the mold, raise the temperature to 90°C, keep it for 2 hours, then raise the temperature to 140°C, keep it for 2 hours, and wait for the material to cool naturally to obtain the epoxy resin composite material.
[0032] Example 2
[0033] An epoxy resin composite material with inorganic materials comprises the following raw materials in parts by weight: 90 parts of E44 epoxy resin, 6 parts of shell-core inorganic material, 18 parts of curing agent polyetheramine D400, and 8 parts of curing accelerator imidazole;
[0034] The epoxy resin composite material is prepared by the following method:
[0035] Step 1: Take 10 parts by weight of E44 epoxy resin and curing agent polyetheramine D400, place them in a stirring kettle, stir them at a temperature of 65° C. for 1 hour, add 10 parts by weight of shell-core inorganic material, continue stirring for 1 hour, then add 10 parts by weight of curing accelerator imidazole, stir and mix for 1 hour, and then stand to degas to form a premixed material;
[0036] Step 2: Pour the premixed material into the mold, raise the temperature to 95°C, maintain it for 2 hours, then raise the temperature to 145°C, maintain it for 3 hours, and wait for the material to cool naturally to obtain the epoxy resin composite material.
[0037] Example 3
[0038] An epoxy resin composite material with inorganic materials comprises the following raw materials in parts by weight: 95 parts of E51 epoxy resin, 10 parts of shell-core inorganic material, 20 parts of curing agent polyamide, and 10 parts of curing accelerator imidazole;
[0039] The epoxy resin composite material is prepared by the following method:
[0040] Step 1: Take 10 parts by weight of E51 epoxy resin and curing agent polyamide, place them in a stirring kettle, stir them at a temperature of 70°C for 2 hours, add 10 parts by weight of shell-core inorganic material, continue stirring for 2 hours, then add 10 parts by weight of curing accelerator imidazole, stir and mix for 1 hour, and then stand to degas to form a premixed material;
[0041] Step 2: Pour the premixed material into the mold, raise the temperature to 100°C, maintain it for 3 hours, then raise the temperature to 150°C, maintain it for 3 hours, and wait for the material to cool naturally to obtain the epoxy resin composite material.
[0042] Comparative Example 1
[0043] An epoxy resin composite material comprises the following raw materials in parts by weight: 90 parts of E44 epoxy resin, 6 parts of montmorillonite, 18 parts of curing agent polyetheramine D400, and 8 parts of curing accelerator imidazole;
[0044] The epoxy resin composite material is prepared by the following method:
[0045] Step 1: Take 1 part by weight of E44 epoxy resin and curing agent polyetheramine D400, place them in a stirring kettle, stir them at a temperature of 65°C for 1 hour, add 1 part by weight of montmorillonite, continue stirring for 1 hour, then add 1 part by weight of curing accelerator imidazole, stir and mix for 1 hour, and then stand to degas to form a premixed material;
[0046] Step 2: Pour the premixed material into the mold, raise the temperature to 95°C, maintain it for 2 hours, then raise the temperature to 145°C, maintain it for 3 hours, and wait for the material to cool naturally to obtain the epoxy resin composite material.
[0047] Comparative Example 2
[0048] An epoxy resin composite material comprises the following raw materials in parts by weight: 90 parts of E44 epoxy resin, 18 parts of curing agent polyetheramine D400, and 8 parts of curing accelerator imidazole;
[0049] The epoxy resin composite material is prepared by the following method:
[0050] Step 1: Take 10 parts by weight of E44 epoxy resin and curing agent polyetheramine D400, place them in a stirring kettle, stir them at a temperature of 65° C. for 1 hour, then add 10 parts by weight of curing accelerator imidazole, stir and mix for 1 hour, and then stand to degas to form a premixed material;
[0051] Step 2: Pour the premixed material into the mold, raise the temperature to 95°C, maintain it for 2 hours, then raise the temperature to 145°C, maintain it for 3 hours, and wait for the material to cool naturally to obtain the epoxy resin composite material.
[0052] The core-shell inorganic material in the above embodiment is prepared by the following method:
[0053] Step 1: Mix 1.6 g of montmorillonite with an average particle size of 5 μm with tetrahydrofuran, stir to form a uniform dispersion, add 1.2 g of 4-bromobutyryl chloride to the dispersion, pass nitrogen protection, start stirring, stir at room temperature for 6 hours, centrifuge to obtain a solid product, wash and dry to obtain intermediate material ①;
[0054] Step 2: Disperse 1.5g of montmorillonite intermediate material ① in 1,4-dioxane, add 1.3g of diallyl isocyanurate and 0.5g of triethylamine and stir evenly, under nitrogen protection, stir and react at a reaction temperature of 65°C for 5h, cool and discharge to obtain intermediate material ②;
[0055] Step 3: Mix 0.8 g of intermediate material ② with ethanol, stir until evenly distributed, then add 2.2 g of 2-(2-hydroxy-3-tert-butyl-5-methylbenzyl)-4-methyl-6-tert-butyl acrylate and stir evenly, raise the system temperature to 75°C, pass nitrogen to deoxygenate, then add 0.1 g of azobisisobutyronitrile, react at constant temperature for 4 hours, separate the material, and obtain the core-shell inorganic material through washing and drying processes.
[0056] The following performance tests were performed on the epoxy resin composite materials prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 and 2:
[0057] Refer to GB / T1040.1-2018, set the tensile rate to 50mm / min, and conduct tensile performance test; refer to GB / T1843-2008, conduct impact performance test; place the material in an accelerated aging box, set the temperature to 180℃, the humidity to 90%, take it out after accelerated aging for 8h, use CS-200 colorimeter to record the color difference value before and after aging of the material, the test results are shown in the table below:
[0058]
[0059]
[0060] From the test results, the epoxy resin composite materials prepared by Examples 1 to 3 of the present invention have good mechanical properties, good toughness, excellent aging and yellowing resistance, and good comprehensive performance. The epoxy resin composite material prepared in Comparative Example 1 uses unmodified montmorillonite as a filler, which cannot form a hydrogen bond network, has poor dispersibility, and has relatively average stress dispersion and transfer effects. Therefore, the mechanical properties, toughness, and aging and yellowing resistance are all average. Comparative Example 2 does not add montmorillonite, and cannot take advantage of the advantages of montmorillonite itself, so the performance of each performance is the worst.
[0061] Based on the ideal embodiment of the present invention, through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.
Claims
1. An epoxy resin composite material with inorganic materials, characterized in that: The method comprises the following raw materials in parts by weight: 85-95 parts of epoxy resin, 5-10 parts of core-shell inorganic material, 12-20 parts of curing agent, and 5-10 parts of curing accelerator; The core-shell inorganic material is prepared by the following method: Step 1: Mix montmorillonite and tetrahydrofuran, stir to form a uniform dispersion, add acyl chloride compound to the dispersion, pass nitrogen protection, start stirring, stir at room temperature for 4-8 hours, centrifuge to obtain solid product, wash and dry to obtain intermediate material ①; Step 2: Disperse the montmorillonite intermediate material ① in 1,4-dioxane, add diallyl isocyanurate and the catalyst and stir evenly, under nitrogen protection, at a reaction temperature of 60-70°C, stir and react for 4-6 hours, then cool and discharge the material to obtain the intermediate material ②; Step 3: Mix the intermediate material ② with ethanol, stir until uniformly distributed, then add 2-(2-hydroxy-3-tert-butyl-5-methylbenzyl)-4-methyl-6-tert-butyl phenyl acrylate and stir evenly, raise the system temperature to 70-75°C, pass nitrogen to deoxygenate, then add the initiator, react at constant temperature for 2-6 hours, separate the material, wash and dry it, and obtain the core-shell inorganic material; In the first step, the acyl chloride compound is any one of bromoacetyl chloride, 3-bromopropionyl chloride or 4-bromobutyryl chloride; In the second step, the catalyst is any one of triethylamine or pyridine; In the third step, the initiator is any one of azobisisobutyronitrile, azobisisovaleronitrile or azobisisoheptanenitrile.
2. The epoxy resin composite material with inorganic material according to claim 1, characterized in that: The epoxy resin is any one of E51 epoxy resin and E44 epoxy resin.
3. The epoxy resin composite material with inorganic material according to claim 1, characterized in that: The curing agent is any one of polyamide or polyetheramine D400.
4. The epoxy resin composite material with inorganic material according to claim 1, characterized in that: The curing accelerator is any one of imidazole and tertiary amine.
5. The epoxy resin composite material with inorganic material according to claim 1, characterized in that: In the first step, the average particle size of the montmorillonite is 5 um.
6. A method for preparing an epoxy resin composite material with inorganic materials as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1: Take 10 parts by weight of epoxy resin and curing agent, place them in a stirring kettle, stir them at a temperature of 60-70°C for 1-2 hours, add 10 parts by weight of shell-core inorganic material, continue stirring for 1-2 hours, then add 10 parts by weight of curing accelerator, stir and mix for 0.5-1 hour, and then stand to degas to form a premixed material; Step 2: Pour the premixed material into the mold, raise the temperature to 90-100°C, maintain it for 2-3 hours, then raise the temperature to 140-150°C, maintain it for 2-3 hours, and wait for the material to cool naturally to obtain the epoxy resin composite material.
Citation Information
Patent Citations
Epoxy resin for closed composite apparatus and preparation method thereof
CN114773789A
Preparation method of exfoliated montmorillonite-epoxy resin composite
CN102061061A
Modified epoxy resin system for carbon fiber boards for pultrusion structure reinforcement
CN103665758A
Low-temperature toughened PVC drainage pipe material, preparation method and application thereof
CN104130525A
Layered inorganic filler / epoxy resin nanocomposite material and preparation method thereof
CN106751480A